2020
DOI: 10.3390/met10050562
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Hydrogen Absorption Behaviour of Metal Alloys Prepared through Mechanical Alloying

Abstract: Hydride-forming alloys are currently considered reliable and suitable hydrogen storage materials because of their relatively high volumetric densities, and reversible H2 absorption/desorption kinetics, with high storage capacity. Nonetheless, their practical use is obstructed by several factors, including deterioration and slow hydrogen absorption/desorption kinetics resulting from the surface chemical action of gas impurities. Lately, common strategies, such as spark plasma sintering, mechanical alloying, mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Ali et al [ 56 ] introduced CoTiO 3 to MgH 2 and showed that the particle size of the composite changed to a finer and smaller size. According to the research results of Somo et al [ 63 ], smaller particle sizes allow quick dissociation into the surface of materials. Besides that, the addition of Nb to MgH 2 creates a large number of hydrogen diffusion channels and speeds up hydrogen flow along the MgH 2 /Mg interfaces, continuing to improve the sorption kinetics of MgH 2 [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ali et al [ 56 ] introduced CoTiO 3 to MgH 2 and showed that the particle size of the composite changed to a finer and smaller size. According to the research results of Somo et al [ 63 ], smaller particle sizes allow quick dissociation into the surface of materials. Besides that, the addition of Nb to MgH 2 creates a large number of hydrogen diffusion channels and speeds up hydrogen flow along the MgH 2 /Mg interfaces, continuing to improve the sorption kinetics of MgH 2 [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The loss of hydrogen capacity of the material after the grinding process was ascribed to these amorphous-like structures, where hydrogen cannot be placed. Somo et al reported in a review about mechanical milling applied to metal alloys that as-milled alloys are more prone to oxide layer formation, hindering the fast hydrogen absorption, and in several cases, diminishing the capacity [74]. Hence, a non-energetic mixing procedure was chosen as the most feasible method for laboratory and larger scales.…”
Section: Discussionmentioning
confidence: 99%
“…A second article revises the hydrogen absorption behavior and the absorption/desorption kinetics of metal hydrides produced by mechanical alloying [8]. It is a critical overview on the effect of mechanical alloying in binary (CaH 2 , MgH 2 , etc.)…”
Section: Contributionsmentioning
confidence: 99%